2020
DOI: 10.2196/18236
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Associations Between Working Time Arrangements and Psychiatric Treatment in Denmark: Protocol for a Cohort Study

Abstract: Background The burden of mental ill health in working-age populations has prompted research on possible links between work-related factors and mental ill health. Long working hours and night shift work are some of the factors that have been studied in relation to the risk of developing mental ill health. Yet, previous studies have not generated conclusive evidence, and further studies of high quality are needed. Objective This study aims to investigate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The analyses were governed by a study protocol ( 6 ) that was accepted for publication before we linked the exposure data of the project to its outcome data. The analyses were, however, not completely blinded since the exposure data of the project have previously been analyzed in relation to ischemic heart disease ( 34 ), stroke ( 35 ), injuries ( 36 ) and all-cause mortality ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The analyses were governed by a study protocol ( 6 ) that was accepted for publication before we linked the exposure data of the project to its outcome data. The analyses were, however, not completely blinded since the exposure data of the project have previously been analyzed in relation to ischemic heart disease ( 34 ), stroke ( 35 ), injuries ( 36 ) and all-cause mortality ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present paper, we will only give a brief description of the material and methods of the study. A detailed description can be found in our study protocol ( 6 ), which was peer-reviewed and published before we commenced with the analysis. The protocol defines two major studies, one of them focuses on effects of long working hours (reported here) while the other focuses on effects of night shift work (results to be reported elsewhere).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Under the null hypothesis, we expected to find approximately 29 new cases of psychotropic drug usage and 3.4 new cases of psychiatric hospital treatment for mood, anxiety, or stress-related disorders per 1000 person-years at risk [ 50 ]. If we assume that approximately 15% of the otherwise eligible participants will be excluded due to exclusion criteria 1-4, the total number of expected cases in the concerned exposure categories will be approximately as shown in Table 4 .…”
Section: Methodsmentioning
confidence: 99%